Rewarming affects EEG background in term newborns with hypoxic–ischemic encephalopathy undergoing therapeutic hypothermia. Issue 4 (April 2016) - Birca, Ala; Lortie, Anne; Birca, Veronica; Decarie, Jean-Claude; Veilleux, Annie; Gallagher, Anne; Dehaes, Mathieu; Lodygensky, Gregory A.; Carmant, Lionel
Highlights: EEG background evolves during rewarming in neonates cooled for hypoxic–ischemic encephalopathy (HIE). Rewarming induced EEG discontinuity is worse in severe compared to moderate HIE. In moderate HIE, rewarming increases delta and decreases alpha/theta EEG activity. Abstract: Objective: To investigate how rewarming impacts the evolution of EEG background in neonates with hypoxic–ischemic encephalopathy (HIE) undergoing therapeutic hypothermia (TH). Methods: We recruited a retrospective cohort of 15 consecutive newborns with moderate (9) and severe (6) HIE monitored with a continuous EEG during TH and at least 12 h after its end. EEG background was analyzed using conventional visual and quantitative EEG analysis methods including EEG discontinuity, absolute and relative spectral magnitudes. One patient with seizures on rewarming was excluded from analyses. Results: Visual and quantitative analyses demonstrated significant changes in EEG background from pre- to post-rewarming, characterized by an increased EEG discontinuity, more pronounced in newborns with severe compared to moderate HIE. Neonates with moderate HIE also had an increase in the relative magnitude of slower delta and a decrease in higher frequency theta and alpha waves with rewarming. Conclusions: Rewarming affects EEG background in HIE newborns undergoing TH, which may represent a transient adaptive response or reflect an evolving brain injury. Significance: EEG background impairment induced by rewarming may represent a biomarker of evolving encephalopathy in HIE newborns undergoing TH and underscores the importance of continuously monitoring the brain health in critically ill neonates.